Synergistic effect of (3-Aminopropyl)Trimethoxysilane treated ZnO and corundum nanoparticles under UV-irradiation on UV-cutoff and IR-absorption spectra of acrylic polyurethane based nanocomposite coating. (January 2019) - Mhd Haniffa, Mhd Abd Cader; Ching, Yern Chee; Chuah, Cheng Hock; Ching, Kuan Yong; Liou, Nai-Shang
Abstract: ZnO and corundum (α–Al2 O3 ) nanoparticles were successfully synthesized by aqueous precipitation and sintering techniques respectively. ZnO nanoparticles were effectively coated with (3-aminopropyl)trimethoxysilane (APTMS) by polycondensation method to prevent the photocatalytic activity of ZnO during a UV-weathering study. X-ray diffractogram and FTIR were used to confirm the crystalline structure of as prepared nanoparticles, blue shift of the AlO bond and the formation of a secondary amine via polycondensation of APTMS over ZnO surface. The prepared APTMS-ZnO, corundum and commercially available surface modified hydrophobic SiO2 (M − SiO2 ) nanoparticles were used to prepare the acrylic polyurethane (AP: Poly-Macrynal ® SM 510 N coating resign) bases nanocomposite coating on a polyurethane substrate. Individual and mixed nanoparticles were dispersed into acrylic polyurethane to prepare the coating layer on polyurethane film substrate separately. IR-active and UV–visible regions of the FTIR and UV–Vis spectroscopies were used to investigate the synergistic effect of the nanoparticles on a selected range of the radiative spectrum, especially the UV-resistant and IR-absorption properties of the coated films with and without exposure of UV-irradiations. Polyurethane substrate coated with APTMS-ZnO (2 wt%) based acrylic polyurethane-based nanocomposite coating (APUC) layer containing 2 wt% corundum (D50) and 6 wt% M − SiO2 (F50) exhibited 98.77% and 97.60% of UV-resistant property respectively. These results indicate that the visible light transparency and transmittance ability reduced significantly after 500 h of UV-irradiation exposure. Both of the activity and deformation have great impact on the IR-absorption property of the APUC. Highlights: Corundum and a secondary amine based APTMS coated ZnO nanoparticles were successfully synthesized. Charge-transfer activity and the intrinsic absorption property of corundum were observed under UV-irradiation exposure. The IR-absorption properties and chemical bonding of the nanocomposite film were studied after weathering test. UV and IR absorption of APTMS-ZnO based APUCs are affected by both of the addition of corundum and M-SiO2 nanoparticles.